Strategy and Impact of Development of the Tasi Oetuke Tourist Attraction on Economic Conditions in Oetuke Village, TTS Regency - Yomestrin Kause; Fransina W. Ballo; Maria Indriyani Hewe Tiwu (Formosa Journal of Applied Sciences, 2023)
This research aims to find out what kind of tourist attraction development strategies are carried out by the local government in the tourist attraction area and its impact on the community in Oetuke Village. This type of research uses field research, which is descriptive qualitative in nature. where data collection uses observation, interview and documentation methods, and all data is analyzed using SWOT analysis (Strength, Weakness, Opportunity, Threat). The results obtained from this research are that the strategy used is to empower the community such as tourism awareness, in addition to improving facilities and infrastructure, carrying out promotions in various media and electronics, as well as improving infrastructure and its impact on the economy of the community in Oetuke Village in increasing income. which are near tourist attractions and levies can help BUMDES administrators to develop tourist attractions.